Keamanan Kunci Ruang Dosen Elektro UMSIDA Menggunakan Ketukan Berbasis Arduino - FahrizaI Akbarlillah Perdana Buana; Indah Sulistiyowati (FT- UNDAR, 2020)
The development of modern technology now are much more advanced and it can make doing a job much easier such as security problems for door locks that are applied to the electrical lecturer room UMSIDA. This tool is designed to run a solenoid lock by using a knock code applied to the door locking system by using microcontroller and piezo electric sensor which will be seen with a security system with knock method. The purpose of this study was to determine the constraints of the door safety device using an electric piezo sensor based on the Atmega328 microcontroller and the system can correctly recognize the beat pattern received and process it. This tool system works when there is an input in the form of a password code through the beats detected by electric piezo if the password code is applied correctly then the microcontroller provides input on relay to activate the solenoid and stepper motor, so the door would open. The result of this research shows that it can identify the correct number of beats a maximum of 15 beats, if it is more than 15 times the beat is wrong. From the result of the trial, fast or not a knock is declared true if the beat time ratio is slow by 4 times knock and the door opens. If the knock pattern is different from what has been determined, then the knock is declared wrong and the door can not open. The test results indicated that it can be concluded that from the test or trial carried out by the object provides true overall results even though the results do not provide 100% results. The results of the analysis of the trial carried out by each objects for 15 times, which affects fast or slow beats, number of beats, the ratio of time between knock